In situ construction and post-electrolysis structural study of porous Ni2P@C nanosheet arrays for efficient water splitting. Issue 16 (14th July 2020) - Ma, Min; Zheng, Zhiping; Song, Zhijia; Zhang, Xibo; Han, Xiao; Chen, Hanming; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract : Carbon-confined Ni2 P porous nanosheet arrays functioned as a superior water-splitting catalyst. Impressively, this porous-hybrid catalyst just required an OER overpotential of 243 mV to deliver 15 mA cm −2 owing to the formation of γ-NiOOH layer. Abstract : In this study, a porous hybrid catalyst with carbon-confined Ni2 P porous nanosheet arrays supported on nickel foam (Ni2 P@C NAs/NF) was developed via a one-step phosphorization of NiMOF precursor. Remarkably, the as-fabricated Ni2 P@C NAs/NF exhibited superior oxygen evolution reaction (OER) performance and only required a small overpotential of 243 mV to deliver a current density of 15 mA cm −2, which surpassed most reported noble-metal-free based OER catalysts working in alkaline media. Such striking results could be ascribed to the synergistic effect between the interconnected macroporous structure (facilitating mass transport and exposing rich accessible catalytic centers) and the modulated electronic states induced by electron transfer from the carbon matrix to nickel phosphide (optimizing its intrinsic electrocatalytic property). In particular, the alkaline two-electrode water electrolyser, which was assembled by simultaneously utilizing Ni2 P@C NAs/NF as the cathode and anode, showed considerable water-splitting activity and durability. Additionally, systematic post-electrolysis structural study confirmed the in situ formation of a γ-NiOOH film on the Ni2 P surface at the anode. This work provides a deep insight into the post-electrolysis structure of nickel-containing catalyst materials and would be helpful for the design of three-dimensional porous hybrid nanocatalysts.